(untitled) (Medical Forum Monthly, 2024)
Objective: To study the pattern of hollow abdominal visceral injuries during minimally invasive gynecological procedures. Study Design: Retrospective, Descriptive Study. Place and Duration of Study: This study was conducted at Fauji Foundation Hospital Karachi, Gulshan General Hospital Karachi, Star General Hospital Karachi and Al-Tibri Medical College Hospital from July 1997 to December 2013. Materials and Methods: All patients admitted to above mentioned hospitals for minimally invasive gynecological procedures electively or in emergency were included in the study. Results: Total 3050 minimally invasive gynecological procedures were carried out in the above mentioned hospitals and 77 (2.5 %) patients had complications following the procedures. Mean age was 28 years ranged from 20-55 years. 40 % patients had history of previous gynaecological surgery.Abdominal visceral injuries included small bowel perforation 30 (38.96 %) patients, sigmoid colon perforation 20 (25.97%)patients. Both small bowel and sigmoid colonic perforation 08 (10.38%) patients, Caecal perforation 01(1.29 %) patient and Urinary Bladder 01 (1.29%) patient. 52 % cases were diagnosed within two days of primary surgery and rest within 10 days. Conclusion: All gynecologists must be skilled, vigilant and careful while doing minimally invasive gynecological procedures that visceral injury should not happen or ready to deal if it happens accidentally.